2023
DOI: 10.1161/circulationaha.122.061955
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dissection of Chamber-Selective Enhancers Reveals Estrogen-Related Receptor as a Regulator of Ventricular Cardiomyocyte Identity

Abstract: BACKGROUND: Cardiac chamber-selective transcriptional programs underpin the structural and functional differences between atrial and ventricular cardiomyocytes (aCMs and vCMs). The mechanisms responsible for these chamber-selective transcriptional programs remain largely undefined. METHODS: We nominated candidate chamber-selective enhancers (CSEs) by determining the genome-wide occupancy of 7 key cardiac transcription factors (GATA4, MEF2A, MEF2C, NKX2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…These observations are consistent with the well-established ERR function in transcriptional activation of FAO and mitochondrial genes and its recently identified role in muscle contraction. 13,43,69,70 Among the large number of downregulated DEGs, we found marked enrichment in pathways that are essential for cell proliferation and developmental processes, such as cell cycle, focal adhesion, extracellular matrix-receptor interaction, DNA replication, and Hippo signaling. 71 Reactivation of cell cycle and fetal gene expression has been causally linked to the development of cardiomyopathy and HF [72][73][74] ; thus, suppression of fetal gene expression could be beneficial for HF.…”
Section: Rna-seq Revealed That Err Agonists Upregulate Fao and Oxphos...mentioning
confidence: 94%
“…These observations are consistent with the well-established ERR function in transcriptional activation of FAO and mitochondrial genes and its recently identified role in muscle contraction. 13,43,69,70 Among the large number of downregulated DEGs, we found marked enrichment in pathways that are essential for cell proliferation and developmental processes, such as cell cycle, focal adhesion, extracellular matrix-receptor interaction, DNA replication, and Hippo signaling. 71 Reactivation of cell cycle and fetal gene expression has been causally linked to the development of cardiomyopathy and HF [72][73][74] ; thus, suppression of fetal gene expression could be beneficial for HF.…”
Section: Rna-seq Revealed That Err Agonists Upregulate Fao and Oxphos...mentioning
confidence: 94%
“…Recent work aimed at identifying important regulators of chamber identity uncovered the TBOX motif as an enriched motif in atrial-specific enhancers and demonstrated elevated expression of Tbx5 in aCMs compared to vCMs 3 . Other studies demonstrated that TBX5 is required for expression of atrialspecific genes, including Nppa and Bmp10 25 .…”
Section: Tbx5 Promotes Acm Identitymentioning
confidence: 99%
“…To better understand changes in the atrial gene expression profile, we examined bulk RNA-seq of atrial tissue from a previous study of adult ubiquitous Tbx5 knockout 17 . We compared differentially expressed left atrial genes to sets of genes with aCM-selective or vCM-selective expression as defined by RNA sequencing of purified cardiomyocytes from each chamber (|fold change| > 1.5, Padj < 0.05) 3 . Gene set enrichment analysis with aCM-selective genes revealed statistically significant reduction in Tbx5 knockout atria (Fig.…”
Section: Tbx5 Promotes Acm Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the initial solid organs in human embryo, the heart displayed a remarkable level of the regulon activity of ESRRG, which is tied to the maturation of cardiac myocytes and maintenance of ventricular identity 38,39 , between PCW3-6 (Fig. 2M-N).…”
Section: Spatiotemporal Dynamics Of Representative Gene Regulatory Ne...mentioning
confidence: 99%